Happiness, Psychology, and Degrees of Realism - Lavazza, Andrea (Frontiers in Psychology, 2016)
The recent emphasis on a realist ontology that cannot be overshadowed by subjectivist or relativist perspectives seems to have a number of consequences for psychology as well. My attempt here is to analyse the relationship between happiness as a state of the individual and the states of the external world and the brain events related to (or, in some hypotheses, causally responsible for) its occurrence. It can be maintained that different degrees of realism are suitable to describe the states of happiness and this fact might have relevant psychological implications, namely for the so-called positive psychology. This is especially true now that there are methods available to induce subjective states of happiness unrelated to the external conditions usually taken to be linked to such states.